An overview of Zn-catalyzed enantioselective aldol type C–C bond formation. Issue 76 (19th August 2015) - Thankachan, Amrutha P.; Asha, S.; Sindhu, K. S.; Anilkumar, Gopinathan
<x xml:space="preserve">Abstract</x> Enantioselective zinc-catalyzed aldol reactions provide an efficient route for the construction of a wide range of carbon–carbon bond-formation, which are described here.